Watching and Making Films with Young People from the Santa Cruz Neighborhood-RJ: Creation Experiences with REALIZACINE - Moreira, Leonardo Cesar Alves; Gomes, Daniele; Cupolillo, Pedro de Almeida; Chamusca, Caroline Montezi de Castro (Farol, 2024)
This paper aims to present the creative experiences mobilized since Realizacine, a cultural project for introducing cinema and audiovisual media to children and young people from the Santa Cruz neighborhood, in the west zone of the city of Rio de Janeiro. To this end, we make some notes about the plurality of these young people and their ways of occupying this territory, presenting audiovisual creation as a possibility of redefining narratives.